Return to work after breast cancer diagnosis: An observational prospective study in Brazil. Issue 24 (17th October 2018) - Landeiro, Luciana C. G.; Gagliato, Debora M.; Fêde, Angelo B.; Fraile, Natalia M.; Lopez, Rossana M.; da Fonseca, Leonardo G.; Petry, Vanessa; Testa, Laura; Hoff, Paulo M.; Mano, Max S.
Abstract : Background: In North America and Europe, return‐to‐work (RTW) rates vary among breast cancer (BC) survivors, from 24% to 66% and from 53% to 82% at 6 and 36 months after diagnosis, respectively. To date, there is a lack of data on RTW rates after BC diagnosis in Latin America. Therefore, the primary objectives of this study were to define RTW rates at 12 and 24 months after BC diagnosis and to identify the factors associated with RTW in this population. Methods: In total, 125 employed women from a single institution with newly diagnosed BC were interviewed by telephone at 6, 12, and 24 months after diagnosis. Those who had inoperable or metastatic disease were excluded. Results: Overall, RTW rates were 30.3% and 60.4% at 12 and 24 months after BC diagnosis, respectively. Most women reported that they received support from their employer, but only 29.1% reported having been offered work adjustments. In multivariate analysis, the factors associated with positive RTW outcomes included higher household income (odds ratio [OR], 17.76; 95% confidence interval [CI], 3.33‐94.75; P = .001), breast‐conserving surgery (OR, 9.77; 95% CI, 2.03‐47.05; P = .004), and work adjustments (OR, 37.62; 95% CI, 2.03‐47.05; P = .004). The factors associated with negative RTW outcomes included adjuvant endocrine therapy (OR, 0.11; 95% CI, 0.02‐0.74; P = .023), and depression diagnosed after BC (OR, 0.07; 95% CI, 0.01‐0.63; P = .017). Conclusions: RTW rates in the current study were lower than those observed in developed countries but similar to the rates among low‐income Americans. Workplace adjustments, higher income, breast‐conserving surgery, endocrine therapy, and depression after BC played an important role in the RTW decision. Abstract : After a diagnosis of breast cancer, return‐to‐work rates among Latin Americans appear to be lower than those observed in developed countries but similar to those in low‐income North Americans. Workplace adjustments, higher household income, breast‐conserving surgery, endocrine therapy, and depression after diagnosis play important roles in the decision to return to work.